Phlebectasia of Internal Jugular Vein - Bindal, Satish K. (Medknow Publications & Media Pvt Ltd, 2012)
Internal jugular phlebectasia (IJP) is a rare disease in which there is a fusiform dilatation of internal jugular vein, usually presenting as a neck mass in children. Accurate diagnosis from careful history, physical examination, and radiological study can be made. We report a 12-year-old boy with history of swelling appearing on the right side of the neck only on straining, coughing, or during a Valsalva maneuver. Diagnosis of right IJP was made. Exploration and wrapping the dilated segment in an 8-mm-diameter polytetrafluoroethylene tube graft was done. Because of its rarity, this entity is frequently ignored or misdiagnosed. This case report intends to stress the importance of keeping IJP as differential diagnosis while dealing with such a swelling to avoid invasive investigations and inappropriate treatment.